Exploring the motivation, goals and contradictions faced by employment equity and transformation practitioners in the South African corporate environment - Oakley-Smith, John Lucien (My University, 2016)
This study explored the personal goals and motivation behind employment equity implementers working within this field and one or more of three broad areas namely: 1) Transformation, 2) Empowerment, and 3) Diversity. The study aimed to explore what it is (ultimately) that these individuals are working for and towards in their day to day lives and professional roles. Were they working towards bigger goals than just compliance with the Employment Equity Act and if so- what were these? Further, the study looked to explore the results of operating in an environment where there are very often competing goals and visions of success, with a final view to understanding what personal tactics and methods implementers deploy to cope and succeed in this context- should an environment of conflicting, competing or contradictory goals exist. The research methodology was a content analysis of in depth semi structured individual interviews. The analysis highlighted the varied views, end goals and conceptual understandings on part of implementers. In every case however a sense of duty or calling emerged which seemed to serve as the key motivator and source of resilience in trying and complex situations. The role constructions that participants undertook also varied and seemed to be linked to the initiatives they busied themselves with as well as their personal motivations in terms of their work. All interviewees experienced some degree of dissonance and or tension between their ultimate goals and views of the subject area from the organisations in which they worked, with different personal responses manifesting
"Employment equity implementers in South Africa: checking boxes or building a shared future?"
Dissertation submitted in fulfilment of the requirements for the Degree: Masters in Psychology by Research, University of the Witwatersrand, Faculty of Humanities
Keywords: Diversity in the workplace--South Africa; Affirmative action programs--South Africa; Minorities--Employment--South Africa